Smartlog – A declarative language for distributed programming in smart grids. (December 2019) - Nguyen, Thi-Thanh-Quynh; Debusschere, Vincent; Bobineau, Christophe; Giap, Quang Huy; Hadjsaid, Nouredine
Abstract: In the control and supervision of smart grids, the objective is to handle any change in the system as fast as possible, with as few resources as possible. In this context, this paper proposes a new language, called Smartlog, designed with a declarative approach. This avoids collecting and analyzing data presenting no interest, and thus being less efficient in bandwidth usage and computational time. Smartlog is designed for operating smart grids defined as abstract structures of large and scalable distributed databases. From its definition, some major properties of this language, such as simplicity, incremental capacity, and scalability are highlighted. The language is tested on the application of the secondary control of an isolated microgrid using a real-time simulator connected to Raspberry Pis. The characteristics of Smartlog are illustrated thanks to a comparison with an imperative programming implementation of the same regulation.